A Multi-Locus Association Model Framework for Nested Association Mapping With Discriminating QTL Effects in Various Subpopulations - Bu, Suhong; Wu, Weiren; Zhang, Yuan-Ming (Frontiers in Genetics, 2021)
Nested association mapping (NAM) has been an invaluable resource for plant genetics community and has yielded insights into the genetic architecture of complex traits. Choosing single-family linkage analysis, joint-multiple family mapping or genome-wide association study (GWAS) is still bewildering for NAM population analysis. A QTL might have ‘schizoid’ effects in different sub-populations, which will particularly confuse the joint-family mapping. Multi-locus association mapping could provide satisfied power in many cases of QTL mapping. Therefore, we developed a multi-locus association model of joint-family for NAM population, which could discriminate the effects of QTLs in all sub-populations. A series of simulations with a set of Maize NAM genomic data demonstrated that new method could satisfactorily improve the statistical power and obtain precise estimate of effects for ‘schizoid’ QTLs. We analyzed the maize NAM data for three flowering time traits with new method and single-family linkage mapping. The results of new method covered nearly most of QTLs from SLM. And some new important QTLs with small effects were detected by the new method.